PENGARUH KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR SEMEN LISTEDBEI 2012-2017 - Resy Mulya Yulitasari; Yulistina Yulistina (Jurnal Media Ekonomi (JURMEK), 2019)
This research aims to examine whether there is an influence between the independent variables on the dependent variable, namely: Quick Ratio, Debt Ratio, Net Profit Margin, and Total Asset Turn Over to Firm Value and Financial Distress and Company Value on Financial Distress both partially and testing together. The data obtained by the authors for the study came from the Indonesia Stock Exchange, namely the company's annual financial statements for the 2012-2017 period. This research was conducted on cement sector companies listed on the IDX with the aim of knowing the Quick Ratio, Debt Ratio, Net Profit Margin, and Total Asset Turn Over Company Value and its impact on Financial Distress by used the Almant Z-Score model and quantitative research methodology. It can be concluded that Quick Ratio and Total Asset Turn Over affect financial conditions while Debt Ratio and Net Profit Margin do not affect the conditions of financial distress